Sperm-binding regions on bovine egg zona pellucida glycoprotein ZP4 studied in a solid supported form on plastic plate. - Kamila Dilimulati; Misaki Orita; Ganbat Undram; Naoto Yonezawa (PLoS ONE)
The zona pellucida (ZP) is a transparent envelope that surrounds the mammalian oocyte and mediates species-selective sperm-oocyte interactions. The bovine ZP consists of the glycoproteins ZP2, ZP3, and ZP4. Sperm-binding mechanisms of the bovine ZP are not yet fully elucidated. In a previous report, we established the expression system of bovine ZP glycoproteins using Sf9 insect cells and found that the ZP3/ZP4 heterocomplex inhibits the binding of sperm to the ZP in a competitive inhibition assay, while ZP2, ZP3, ZP4, the ZP2/ZP3 complex, and the ZP2/ZP4 complex do not exhibit this activity. Here, we show that bovine sperm binds to plastic plates coated with ZP4 in the absence of ZP3. We made a series of ZP4 deletion mutants to study the sperm-binding sites. The N-terminal region, Lys-25 to Asp-136, and the middle region, Ser-290 to Lys-340, of ZP4 exhibit sperm-binding activity. These results suggest that among the three components of bovine ZP glycoproteins, ZP4 contains the major potential sperm-binding sites, and the formation of a multivalent complex is necessary for the sperm-binding activity of ZP4.